Does age matter? Sexual event-level analysis of age-disparate sexual partners among gay, bisexual and other men who have sex with men (GBM) in Vancouver, Canada. (16th November 2016) - Closson, K; Lachowsky, N J; Cui, Z; Shurgold, S; Sereda, P; Rich, A; Moore, D M; Roth, E A; Hogg, R S
Abstract : Background: To determine factors associated with age-disparate sexual partners among Vancouver gay, bisexual and other men who have sex with men (GBM). Methods: Sexually active GBM aged ≥16 years were recruited from February 2012 to February 2014. Participants self-completed a questionnaire on demographics, attitudes and sexual behaviour and substance use at last sexual event with five most recent partners. Two generalised linear mixed models identified factors associated with: (1) 'same-age' (referent), 'younger' or 'much-younger' and (2) 'same-age' (referent), 'older' or 'much-older' partners. Statistical interactions between age and HIV status were tested. Results: Participants (n=719) were predominantly gay (85.1%), White (75.0%), HIV-negative/unknown status (72.9%) with median age of 33 years (Q1, Q3: 26, 47). A minority of sexual events were reported with much-older/much-younger partners (13.7%). In the multivariable models, GBM reporting older partners were more likely to be Asian or Latino, have greater Escape Motivation scores, report their partner used erectile dysfunction drugs (EDDs) and have received something for sex; compared with condom-protected insertive anal sex, participants with older partners were more likely to report condomless insertive anal sex with a serodiscordant or unknown status partner or no insertive anal sex. GBM reporting older partners were less likely to be bisexual-identified, have given something for sex and report event-level alcohol and EDD use. GBM reporting younger partners were more likely to have annual incomes >$30 000 and have met their partner online. As per significant statistical interactions, age-disparate relations were more common for younger HIV-positive and older HIV-negative GBM. Conclusions: Differences among age-disparate partners highlight important targets for health promotion and future research.